1986
DOI: 10.1128/iai.53.1.64-70.1986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunoblot analyses of spherule-endospore-phase extracellular protein and mycelial-phase antigen of Coccidioides immitis

Abstract: The extracellular proteins produced by Coccidioides immitis during growth of the spherule-endospore-phase and mycelial-phase antigen (coccidioidin) were studied by polyacrylamide gel electrophoresis followed by immunoblot analysis to detect specific serologic function. Filtrates obtained from 28-and 120-h growth of the spherule-endospore phase were compared with each other and with coccidioidin by using negative, immunoglobulin M (IgM) precipitin-positive, or complement fixation-positive pooled and single huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…Using a similar approach, Calhoun et al (1) demonstrated reactivity of a 45-to 48-kDa antigen with IDCF-positive sera of coccidioidomycosis patients. We do not yet know if the F antigen isolated in this study is similar or identical to the 48-kDa antigen reported by Zimmer and Pappagianis (21) or the 45-to 48-kDa antigen reported by Calhoun et al (1). Although we have used the technique of immunoblotting to assess the monospecificity of antiserum prepared against the F antigen, we do not believe that this technique is well suited for analyses of the F antigen.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Using a similar approach, Calhoun et al (1) demonstrated reactivity of a 45-to 48-kDa antigen with IDCF-positive sera of coccidioidomycosis patients. We do not yet know if the F antigen isolated in this study is similar or identical to the 48-kDa antigen reported by Zimmer and Pappagianis (21) or the 45-to 48-kDa antigen reported by Calhoun et al (1). Although we have used the technique of immunoblotting to assess the monospecificity of antiserum prepared against the F antigen, we do not believe that this technique is well suited for analyses of the F antigen.…”
Section: Discussionmentioning
confidence: 56%
“…Although we have used the technique of immunoblotting to assess the monospecificity of antiserum prepared against the F antigen, we do not believe that this technique is well suited for analyses of the F antigen. This conclusion is based upon our finding that the F antigen is labile to the conditions used in sodium dodecyl sulfate-polyacrylamide gel electrophoresis which, as pointed out by Zimmer and Pappagianis (21), are required for optimal resolution of CDN components in immunoblots. Although 2D-IEP is less sensitive than immunoblot analyses and is limited to detection of precipitinogens.…”
Section: Discussionmentioning
confidence: 83%
“…The tube precipitin antigen, which frequently reacts with antibodies from patients with coccidioidomycosis, is also detectable on the spherule surface. It has been suggested for that antigen as well that its presentation to host cells may involve the sloughing component of the spherule envelope (9,41).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of coccidioidomycosis is often made on the basis of serological assays employing crude antigens prepared from filtrates or lysates of mycelial or spherule-endospore phases of Coccidioides immitis (25). Currently used qualitative tests include immunodiffusion (ID) for the detection of immunoglobulin M (IgM) (IDTP) or IgG (IDCF) and enzyme immunoassay (EIA) for the detection of these two major antibody responses (4,19).…”
mentioning
confidence: 99%